1998
DOI: 10.1002/(sici)1097-0142(19980401)82:7<1328::aid-cncr16>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Poorer survival of nulliparous women with endometrial carcinoma

Abstract: between parity and the incidence of endometrial carcinoma. A prognostic influence of reproductive factors has been reported for carcinomas of the breast and uterine follow-up information. RESULTS.Nulliparous women had a poorer 5-year survival rate compared with patients who had had 1 or more deliveries (57% vs. 81%, P Å 0.0001), and they were significantly older and had more advanced disease at the time of primary surgery than the parous women. After adjustment for traditional risk factors, a hazard ratio of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
16
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 34 publications
3
16
3
Order By: Relevance
“…1 It has been noted that these tumors have clinical characteristics more similar to high-grade endometrial carcinomas, 1,2,4,5 but differences also exist. 6Y8 Similar to findings for patients with endometrial carcinoma, 9,10 nulliparity was found in 1 study to adversely affect prognosis in patients diagnosed with CS. 11 Two other studies, 12,13 however, could not confirm this finding.…”
supporting
confidence: 63%
“…1 It has been noted that these tumors have clinical characteristics more similar to high-grade endometrial carcinomas, 1,2,4,5 but differences also exist. 6Y8 Similar to findings for patients with endometrial carcinoma, 9,10 nulliparity was found in 1 study to adversely affect prognosis in patients diagnosed with CS. 11 Two other studies, 12,13 however, could not confirm this finding.…”
supporting
confidence: 63%
“…12,13 Diagnostic delay among nulliparous women was considered as a possible explanation in these studies, but seems less likely in the present study because the association with parity seemed to be strongest among women with the most favorable prognosis. In 1 previous study that included surgical stage II tumors only, 17 parity was not a significant predictor of disease recurrence.…”
Section: Discussionmentioning
confidence: 58%
“…In women without any pregnancyrelated protection caused by mechanical 9,10 or hormonal mechanisms, 11 a more advanced disease at the time of diagnosis or an earlier age at onset may be expected. In our previous populationbased study of endometrial cancer patients, 12 however, nulliparity was associated with a worse prognosis in analyses adjusted for age at diagnosis and clinical stage, indicating a more aggressive tumor behavior in patients with no childbirths. Similar findings were reported among older women in a smaller study, 13 but the association was considerably weakened in the analysis adjusted for traditional prognostic factors and diagnostic delay, defined as time interval since initial symptoms.…”
mentioning
confidence: 79%
“…Although stage at diagnosis, histologic type, tumor grade, and other pathologic characteristics of the tumor have been shown to importantly influence prognosis after endometrial cancer (3) , modifiable risk factors for endometrial cancer incidence may also impact survival. Studies of endometrial cancer cases have shown that lower overall mortality rates were associated with higher body mass (4,5) and previous exogenous estrogen use (6,7) , but having diabetes (8) and being nulliparous (9,10) were associated with a higher overall mortality; endometrial cancer–specific mortality has not been described in relation to these factors. In cohorts of healthy women, higher body masses (11,12) , diabetes (13,14) , and exogenous estrogen use (15) were all associated with an increased risk of death, and oral contraceptive use was associated with a slightly reduced risk of death (9,16) , although these associations potentially reflect an influence of both incidence and survival.…”
mentioning
confidence: 99%